A prospective study of hepatitis B virus markers in patients with chronic HBV infection from Brazilian families of Western and Asian origin - Carrilho,F.J. (2005)
The purpose of the present study was to determine the frequency of hepatitis B virus (HBV) markers in families of HBsAg-positive patients with chronic liver disease. Serum anti-HBc, HBsAg and anti-HBs were determined by enzyme immunoassay and four subpopulations were considered: genetically related (consanguineous) and non-genetically related (non-consanguineous) Asian subjects and genetically related and non-genetically related Western subjects. A total of 165 and 186 relatives of Asian and Western origin were enrolled, respectively. The occurrence of HBsAg and anti-HBs antibodies was significantly higher (P < 0.0001) in family members of Asian origin (81.8%) than in family members of Western origin (36.5%). HBsAg was also more frequent among brothers (79.6 vs 8.5%; P < 0.0001), children (37.9 vs 3.3%; P < 0.0001) and other family members (33.9 vs 16.7%; P < 0.0007) of Asian than Western origin, respectivelly. No difference between groups was found for anti-HBs, which was more frequently observed in fathers, spouses and other non-genetic relatives. HBV infection was significantly higher in children of Asian than Western mothers (P < 0.0004). In both ethnic groups, the mothers contributed more to their children's infection than the fathers (P < 0.0001). Furthermore, HBsAg was more frequent among consanguineous members and anti-HBs among non-consanguineous members. These results suggest the occurrence of vertical transmission of HBV among consanguineous members and probably horizontal sexual transmission among non-consanguineous members of a family cluster. Thus, the high occurrence of dissemination of HBV infection characterizes family members as a high-risk group that calls for immunoprophylaxis. Finally, the study showed a high familial aggregation rate for both ethnic groups, 18/19 (94.7%) and 23/26 (88.5%) of the Asian and Western origin, respectively.